Contextualized Financial Numeracy in Mathematics Education: Integrating Local Knowledge Within Global Educational Practices - Nur Maulidiawati Rahman; Sirwanti Sirwanti; Hirpan Hirpan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to explore the integration of financial literacy into context-based mathematics education at the elementary school level by emphasizing the use of local knowledge in learning activities. Employing a qualitative descriptive approach, this research investigates the experiences and perceptions of students and teachers involved in mathematics learning that connects mathematical concepts with real-life financial situations, such as budgeting, saving, and personal financial management. Data were collected through interviews, classroom observations, and documentation analysis to obtain a comprehensive understanding of the learning process and its outcomes. The findings indicate that integrating financial literacy into context-based mathematics learning enhances the relevance of mathematical content and facilitates students’ conceptual understanding. Students reported increased interest and engagement in mathematics lessons, as well as greater confidence in applying mathematical skills to manage personal finances. The use of familiar financial contexts enabled students to perceive mathematics as meaningful and applicable to their daily lives. Teachers identified limited instructional time and difficulties in explaining abstract concepts as key obstacles in the implementation process. Overall, the results suggest that context-based mathematics learning integrated with financial literacy has strong potential to improve students’ mathematical understanding and financial awareness while fostering practical life skills. Nevertheless, effective implementation requires careful instructional planning, adequate time allocation, and appropriate pedagogical strategies to address complex financial concepts. This study contributes to the growing body of research on contextualized mathematics education by highlighting the importance of integrating local context and financial literacy to enhance the quality and relevance of elementary mathematics education.